An evaluation of thermal and lighting performance within an ETFE structure - Martin, Benjamin A.J.; Masih, Dawa; Lau, Benson; Beccarelli, Paolo; Chilton, John (Springer, 2016)
This paper reports on a study into the thermal and lighting environment of an enclosed Ethylene Tetrafluoroethylene (ETFE) foil-covered structure. This is based on the on-site monitoring over set periods of time in summer 2014 and winter 2015. ETFE-foil is a relatively new highly-translucent construction material that has been used in some high profile projects around the world. In a unique development, this project looked at a new building product that makes use ETFE film and tensioned it over aluminium frames to create a modular ETFE-covered panel that can look similar to and can be installed as a replacement for glazing. This opens up new markets for the use of ETFE-film, such as agriculture and horticulture, and allows for possibilities such as urban and vertical farming or the retrofitting of existing commercial and residential greenhouses. A test structure was constructed from the ETFE-covered panels. This paper will report on the impacts of solar radiation on the thermal environment as well as the relative humidity within this enclosure so that a more holistic understanding of the thermal comfort can be obtained. The second section will explore the internal daylighting environment including analysis of the daylight factor within the structure and luminance mapping to examine brightness and visual performance and its effect on the perception of space and objects within. The paper will conclude that the temperature within the enclosed ETFE structure can become too high during the summer months and may require heating when occupied during the winter months. The research also finds that the daylight levels can be too bright if the internal space were to be used regularly by occupants, although this may be beneficial for plants. In both cases, overheating and solar gain issues can be resolved through appropriate shading and ventilation.